The Role of Artificial Intelligence in Enhancing Teachers’ Productivity and Classroom Management - EL KADI, Mohamed; AKRACHI, NADIR (International Journal of Language and Literary Studies, 2026)
The study examines the role of Artificial Intelligence (AI) in enhancing teachers’ productivity and classroom management. For this purpose, a “Systematic Literature Review” of twenty-five (25) research papers was selected to analyse the phenomena. To analyse the data, three major themes were developed: a) AI and Teachers’ productivity, b) AI and classroom management, and c) barriers and challenges teachers face when using AI tools and systems. To give the theoretical foundation, the Technology Acceptance Model (TAM), the Technological Pedagogical Content Knowledge (TPACK), and the Resource-Based View (RBV) were applied. The findings showed that AI enhances overall Teachers’ productivity through advancements in administrative tasks, facilitation of lesson planning and design, content creation, and performance and workload evaluation, ultimately saving time. Moreover, the adoption of AI can enhance classroom management through automation, monitoring and assessment, behavioral tracking, and greater efficiency in the teaching and learning process. However, integration of AI in classroom settings remains challenging for teachers due to insufficient infrastructure, teachers’ resistance, a lack of technical training and skills, data privacy and security issues, ethical considerations, and inadequate institutional support. It can be recommended that implementing various types of training and awareness programs for teachers to enhance their competencies in using AI tools and systems in classroom settings.